Endoscopic mucosal resection using cold snare versus hot snare in treatment for 10–19 mm non-pedunculated colorectal polyps: protocol of a non-inferiority randomised controlled study - Yuelun Zhang; Aiming Yang; Dong Wu; Duan Wang; Shengyu Zhang; Xiaxiao Yan; Qingwei Jiang; Yunlu Feng (BMJ Open, 2023)
Introduction Cold polypectomy has the advantages of simple operation, less time-consuming and fewer complications. Guidelines have recommended cold snare polypectomy (CSP) to resect small polyps sized ≤5 mm and sessile polyps sized 6–9 mm. However, evidence is scarce regarding cold resection for non-pedunculated polyps sized ≥10 mm. Cold snare endoscopic mucosal resection (CS-EMR) combining CSP and submucosal injection was designed to improve the complete resection rate and reduce adverse events. We hypothesise that CS-EMR is non-inferior to conventional hot snare endoscopic mucosal resection (HS-EMR) in the resection of 10–19 mm non-pedunculated colorectal polyps.Methods and analysis This study is a prospective, randomised, open-label, non-inferiority, single-centre trial. Outpatients scheduled to undergo a colonoscopy and present eligible polyps will be randomised to receive either CS-EMR or HS-EMR. The primary endpoint is the complete resection. Considering that HS-EMR of 10–19 mm colorectal polyps will yield a complete resection rate of at least 92% and a non-inferiority margin of −10%, a total of 232 polyps will be included (one-sided α, 2.5%; β, 20%). The analyses are intended to evaluate first non-inferiority (lower limit 95% CI greater than −10% for group difference) and then superiority (lower limit 95% CI>0%) if non-inferiority is achieved. Secondary endpoints include en-bloc resection, the occurrence of adverse events, the use of endoscopic clips, resection time and cost.Ethics and dissemination The study has been approved by the institutional review board of the Peking Union Medical College Hospital (No. K2203). All participants in the trial will provide written informed consent. The results of this trial will be published in an open-access way.Trial registration number NCT05545787.